2002
DOI: 10.1364/josab.19.001476
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz dielectric properties of polystyrene foam

Abstract: We have performed terahertz time-domain spectroscopy measurements on three types of polystyrene foam. We find that between 0.2 and 4 THz, the extinction of this material is low and that it has a remarkably low refractive index of 1.017 to 1.022 in this range, with little variation as a function of frequency. In foam produced with HCFC 142b gas (1-chloro-1,1-difluoroethane) as the blowing agent, we find an additional absorption band at 0.5 THz caused by rotational transitions in this gas. The low extinction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 13 publications
4
51
0
Order By: Relevance
“…Although liquid cells are widely available, they proved unsuitable for the liquid measurements presented here because of their high attenuation of terahertz radiation. Instead, a technique was devised using a polyethylene bag compressed between two pieces of polystyrene known to have low terahertz attenuation [5]. We assumed that attenuation was described by a linear attenuation coefficient, but further investigation will be necessary to gain an understanding scattering of terahertz radiation in tissue and thus determine the conditions under which that assumption is valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although liquid cells are widely available, they proved unsuitable for the liquid measurements presented here because of their high attenuation of terahertz radiation. Instead, a technique was devised using a polyethylene bag compressed between two pieces of polystyrene known to have low terahertz attenuation [5]. We assumed that attenuation was described by a linear attenuation coefficient, but further investigation will be necessary to gain an understanding scattering of terahertz radiation in tissue and thus determine the conditions under which that assumption is valid.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid samples were held in a polyethylene bag, which was compressed between two slices of polystyrene. This material was chosen because in the terahertz band it has low attenuation and a refractive index equal to that of air [5]. A mechanical translation stage was used to change the path length by 25 µm, 50 µm, 75 µm and 100 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The estimated refractive index in polystyrene foam regions ranges from 1.02 to 1.035, and the average is 1.025 (± 0.003). In reference [11], it was reported that the refractive index of polystyrene foam ranges from 1.016 to 1.022. The values are similar to our estimated average value.…”
Section: Resultsmentioning
confidence: 99%
“…After reflecting from several paraboloidal mirrors, the THz beam passes through a 2 mm thick piece of polystyrene foam. The polystyrene foam has a refractive index of 1.017 and an absorption coefficient of less than 1 cm −1 for frequencies below 4 THz, and is thus nearly completely transparent in this frequency range, while blocking any remaining near-infrared 'leaking' around the emitter (Zhao et al 2002). A small, gold-coated, right-angle prism is glued onto the foam.…”
Section: Methodsmentioning
confidence: 99%